A study of ice crystal development in hairtail samples during different freezing processes by cryosectioning versus cryosubstitution method. (March 2018) - Luan, Lanlan; Wang, Liping; Wu, Tiantian; Chen, Shiguo; Ding, Tian; Hu, Yaqin
Highlights: Cryosections enabled facile and rapid observation of ice crystals. Higher freezing rate produced smaller and regular ice crystals in frozen hairtail. Small crystals cause little damage to muscles with higher water holding capacity. Abstract: Hairtail samples were frozen by three different treatments, including conventional air freezing (CAF) at −20  o C, refrigerator cryogenic freezing (RCF) at −80  o C and liquid nitrogen immersion freezing (LIF) at −196  o C. In order to investigate the influence of freezing treatments on the development of ice crystal in hairtail samples, an improved method based on cryosection was applied to observe the formation of ice crystals in frozen hairtail meat, comparing with the traditional method of cryosubstitution. Results showed that cryosectioning was a highly effective tool for intuitionistic view of ice crystals, and greatly shortened the time from 3–5 days to 20–30 min. The equivalent diameter of the ice crystals determined by cryosectioning were 12.6 ± 3.73, 3.62 ± 1.91, and 1.22 ± 0.39 µm for the samples subjected to CAF, RCF and LIF, respectively. Smaller and more regular intracellular ice crystals were observed in hairtail samples frozen by LIF compared with other treatments. The microstructure of three frozen treated samples was profiled by scanning electron microscopy as well. Significant differences were observed in the water holding capacity in frozen samples of CAF (86.8%), RCF (87.4%), and LIF (89.2%). The characteristics of ice crystals, which have a strong influence on the final quality of the food, were considered as an important factor for the quality of hairtail during freezing.